DELVING INTO EFL LEARNERS’ EXPERIENCE OF VOCABULARY MASTERY IN DIGITAL AGE: A NARRATIVE INQUIRY STUDY IN INDONESIA - Islami, Novi Nur; Ismaili, Ismaili (Cahaya Ilmu Bangsa Institute, 2024)
For the past few decades, the research on vocabulary learning and digital mediated learning has attracted the attentions of various researchers. Digital media has been proven to give positive influence on the development of learners’ vocabulary knowledges. However, the study in which investigate on how learners learn vocabulary mediated by various digital media is still in its infancy. Thus, this study is conducted in order to explore how EFL learners learn vocabulary mediated by various digital resources. In doing so, this study employs narrative inquiry and collect the data using semi-structure interview involving two females undergraduate EFL learners in which currently majoring in English Education Department in several Universities in Jember, Indonesia. As results, this study found that both participants employ various vocabulary learning strategies using various digital media. Additionally, this study also found that both participants are highly motivated to learn vocabulary from digital apps. Lastly, limitations and recommendations are also discussed in this study. Keywords: EFL learners Experience; Vocabulary Mastery; Digital Age.